Brussels Studies: 15 jaar en 1,5 miljoen downloads. Momentopnames van een stad en een lokaal wetenschappelijk tijdschrift - Tatiana Debroux; Margaux Hardy (Brussels Studies, 2022)
Brussels Studies recently celebrated its 15th anniversary. While its editorial approach – which is to provide a trilingual platform of academic publications on and for Brussels to a wide readership – has remained unchanged since 2006, many adaptations have taken place over the years and with the 168 articles published so far. The journal has thus succeeded in reaching a varied readership over the years, from the academic world, administrations and public authorities, as well as from the non-profit sector. Brussels Studies is in fact exceptional, in that it makes Brussels one of the few cities in the world with a scientific journal dedicated to it. By means of a few brief facts and figures, this fact sheet takes a retrospective look at the journal's editorial ecosystem, the characteristics of the articles published and the impact they have had on debates and public action.